Reshaping cities from smart to liveable: A taxonomy of measures - Manvi Jain; Srabani Sanyal (National Geographical Journal of India, 2023)
"The quality of life is more important than life itself," poignantly emphasizes that mere existence is not the ultimate goal; instead, the paramount aim is to attain a life characterized by health, happiness, and a high standard of living. Nevertheless, it is a stark reality that a substantial portion of the global population does not have the privilege of experiencing such a quality of life. In pursuit of better opportunities and improved living conditions, people are drawn to urban centers, envisioning them as hubs of promise and growth. However, the rapid urbanization resulting from this migration often leads to haphazard settlement patterns, unchecked population growth, and the inadvertent exacerbation of human-induced environmental issues. These urbanization-related challenges cast a shadow on various facets of urban living, including infrastructure, healthcare accessibility, energy consumption, waste management, and the resilience of cities. Addressing these multifaceted challenges is pivotal in the quest to bridge the gap between mere existence and a life characterized by quality and well-being. The paper intends to comprehend how the notion of livability has evolved since its inception. It also addresses the complex interplay between the quality of life, urbanization, sustainability, and smart city concepts. It seeks to provide a comprehensive understanding of these issues and offer insights into how to measure livability effectively in the context of Indian cities, given their unique challenges and opportunities.